Profile of sheep meat consumers in the municipality of Poço Verde, Sergipe, Brazil (Research, Society and Development, 2022)
This work aims to verify several variables relevant to the consumption of sheep meat, seeking to establish the profile of sheep meat consumers in the city of Poço Verde - SE. In this sense, 50 sheep meat consumers in the municipality were interviewed through a semi-structured multiple-choice questionnaire, from November, 2020, which addressed various aspects related to meat consumption. The information obtained was organized in a Microsoft Excel spreadsheet (2010), for later interpretation of the data obtained. It was obtained as a result that taste is the main limiting reason for a greater frequency of consumption of this meat, as well as variables related to tradition in consumption and the price offered are important factors in the process of purchasing the product in the region. Considering that the places of sale, the little variety and the color of the sheep meat linked to the fat content, also influence the consumption of this product. The work points out the behavior, requirements and perceptions of sheep meat consumers, becoming a fundamental tool for the production chain, since it can be expanded and improved for future research with greater scope.